The deliberative potential of political conversations about the Medical Act Bill on YouTube - ALTHEMAN, Francine; MARTINO, Luís Mauro Sá; MARQUES, Ângela Cristina Salgueiro (Revista Compolítica, 2013)
The aim of this article is to analyze the possible deliberative contributions of political conversations on-line concerning the Medical Act Bill, a regulatory framework of medical profession in Brazil. We have analyzed spontaneously posts on YouTube about two specific videos against the Medical Act Bill: “No Medical Act” and “Just say no to the Medical Act Bill”. The online discussion generated by these videos shows that political conversations online can potentially contribute to the formation of public spheres in which argumentative exchanges are drive by critical and rational justification of points of view, for the revision of perspectives; for the development of communicative and reflexive capacities, and for the exercise of reciprocity